2022
DOI: 10.2196/33235
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Parental Attitudes Toward COVID-19 Vaccination and Routine Childhood Vaccination During the COVID-19 Pandemic: Repeated Cross-sectional Survey Study

Abstract: Background It was reported that one in four parents were hesitant about vaccinating their children in China. Previous studies have revealed a declining trend in the vaccine willingness rate in China. There is a need to monitor the level of parental vaccine hesitancy toward routine childhood vaccination and hesitancy toward the COVID-19 vaccine during the ongoing COVID-19 pandemic. Objective This study aims to assess changes in trends of parental attitud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Worry about vaccine safety and its potential adverse effect [ 56 , 59 , 64 , 65 , 67 , 70 , 72 , 76 , 77 , 81 , 85 , 86 , 90 , 91 , 92 , 94 , 95 , 98 , 101 , 103 , 105 , 112 , 115 , 116 , 118 , 121 , 126 , 127 , 128 , 131 , 132 , 133 , 140 , 142 ], novelty of vaccine and its’ short development time [ 57 , 101 , 116 ], and hesitancy regarding vaccine’s efficacy and benefits [ 56 , 59 , 66 , 70 , 71 , 72 , 74 , 76 , 92 , 94 , 101 , 105 , 115 , 117 , …”
Section: Resultsmentioning
confidence: 99%
“…Worry about vaccine safety and its potential adverse effect [ 56 , 59 , 64 , 65 , 67 , 70 , 72 , 76 , 77 , 81 , 85 , 86 , 90 , 91 , 92 , 94 , 95 , 98 , 101 , 103 , 105 , 112 , 115 , 116 , 118 , 121 , 126 , 127 , 128 , 131 , 132 , 133 , 140 , 142 ], novelty of vaccine and its’ short development time [ 57 , 101 , 116 ], and hesitancy regarding vaccine’s efficacy and benefits [ 56 , 59 , 66 , 70 , 71 , 72 , 74 , 76 , 92 , 94 , 101 , 105 , 115 , 117 , …”
Section: Resultsmentioning
confidence: 99%
“…26,27 These factors caused the anti-vaccine movement to revive after the COVID-19 outbreak. 10,26,27 High rates of vaccine hesitancy against COVID-19, combined with economic difficulties, and growing discomfort with containment measures, serve as an advantage for anti-vaccine campaigners. 6 The anti-vaccine movement has tried to increase parents' hesitations about childhood vaccines by taking advantage of the difficulties experienced due to the COVID-19 pandemic and the high rates of vaccination hesitations against COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…9 A study conducted in China found that the childhood vaccine rejection rates of parents increased from 7.8% in September-October 2020 to 15.1% in February-March 2021 as the impact of the COVID-19 pandemic increased. 10 There is only one study examining the change in parents' hesitation about childhood vaccines during the COVID-19 pandemic. 10 The aim of this study was to examine the changes in parents' attitudes towards childhood vaccines during COVID-19 pandemic.…”
Section: Changes In Parents' Attitudes Towards Childhood Vaccines Dur...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although most reported cases were self-limited and the benefits of the COVID-19 vaccine in preventing COVID-19 and severe disease outweigh the risks of myocarditis, 5,6,8 the concern about myocarditis as a side effect reduces the willingness of adolescents to be vaccinated. 9,10 Therefore, further investigation into cardiac changes after vaccination is needed to establish public trust in vaccines.…”
Section: Introductionmentioning
confidence: 99%